Селянське самоврядування та земство в Росії (друга половина ХІХ – початок ХХ ст. ) - Верховцева, І.Г. (Історичний архів. Наукові студії, 2014)
Охарактеризовано відносини між установами селянського самоврядування та
земством у другій половині ХІХ – на початку ХХ ст. Доведено, що попри значні зусилля
у розбудові господарства і культури села, у відносинах з селянськими установами земства
поводилися зверхньо, поступово з боку останніх брали гору тенденції адміністрування;
недостатньою була увага з боку земців до проблеми станової відокремленості селян в
управлінні місцевостями. Натомість селянські установи через специфічні риси
світосприйняття селянства, його правовий нігілізм та антидержавні настрої,
ототожнюючи земство з імперськими бюрократичними установами, чинили йому опір. Охарактеризованы отношения между учреждениями крестьянского самоуправления
и земством во второй половине ХІХ – начале ХХ в. Доказано, что несмотря на
значительные усилия по хозяйственному и культурному обновлению села, в
отношениях с крестьянскими учреждениями земства демонстрировали верховенство,
постепенно со стороны последних стали преобладать тенденции администрирования;
недостаточным было внимание со стороны земцев к проблеме сословной обособленности
крестьян в управлении своими местностями. Крестьянские же учреждения в силу
специфичности мировосприятия крестьянства, его правового нигилизма и антиго-
сударственных настроений, отождествляя земство с имперскими бюрократическими
учреждениями, сопротивлялись ему. Relations between the institutions of peasant self-government and the zemstvo in the
second half of 19th
– at the beginning of 20th century are characterized. The author proves that
despite of significant efforts in the development of village economy and culture, the zemstvos
demonstrated the “superiority” in relations with the peasant institutions. Gradually trends of
administration prevailed from the latest; attention from the zemstvo members to the problem of
class isolation of farmers in the areas management was insufficient. On the other hand, the
peasant institutions through specific features of peasant mentality, legal nihilism and antigovernment
climate identified zemstvo with imperial bureaucratic institutions. Accordingly, the
peasant institutions were not adjusted on collaboration with zemstvo in life managing of their
areas and they carried out resistance. Through 50 years after introduction of the peasant and
zemstvo self-government institutions there was a gap between them: peasants attitude to the
last was dismissive and under conditions of unauthorized agricultural redistribution they were
plundered property of zemstvo, because they counted it as “master’s”. Exactly zemstvo
remained for peasants as stranger, “unwanted” institution, which, except for new taxes, from
point of peasant, brought in nothing useful in his existence. It had tragic consequences in the
conditions of revolutionary transformations after February 1917, when zemstvo leaders became
reformation initiators and active participants of country government. In particular the system of
zemstvo institutions became the core of a new power structure, to which in May 1917 a new link
was added – volost zemstvo. In fact it was peasant institution, but formally it had all classes’
character. Low level of political culture and education of peasants, sad experience in activity of
class peasant self-government institutions and absence of collaboration experience with
zemstvos, which must be developed over the years during the coexistence of these institutions
and due to what the system of relations must be formed, which would help peasants through
their representatives to integrate to the volosts management, would «include» them in volost
local society, on the background of zemstvos bureaucratization at the end of 19th
– at the
beginning of 20th century, as the author considers, not in the last turn determined horror of
“black redistribution”, robberies, scornful peasants attitude to the laws, state and local power in
turbulent revolutionary times.